LRRK2 is expressed in areas affected by Parkinson's disease in the adult mouse brain - Simón-Sánchez, Javier; Herranz-Pérez, Vicente; Olucha-Bordonau, Francisco; Pérez-Tur, Jordi (The European journal of neuroscience, 2006)
The leucine‐rich repeat kinase 2 (LRRK2) gene was recently found to have multiple mutations that are causative for autosomal dominant inherited Parkinson's disease (PD). Previously, we used Northern blot analysis to show that this gene was expressed in the cerebellum, cerebral cortex, medulla, spinal cord, occipital pole, frontal lobe, temporal lobe and caudate putamen. However, a more comprehensive map of LRRK2 mRNA localization in the central nervous system is still lacking. In this study we have mapped the distribution of the mRNA encoding for LRRK2 using nonradioactive in situ hybridization. We detected a moderate expression of this PD‐related gene throughout the adult B2B6 mouse brain. A stronger hybridization signal was observed in deep cerebral cortex layers, superficial cingulate cortex layers, the piriform cortex, hippocampal formation, caudate putamen, substantia nigra, the basolateral and basomedial anterior amygdala nuclei, reticular thalamic nucleus and also in the cerebellar granular cell layer. Given that LRRK2 mRNA is highly enriched in motor systems and also is expressed in other systems, we may conclude that mutations in LRRK2 may affect several motor and nonmotor structures that may play an important role in the development of PD.